Different Types of Hyperfluorescence Observed in Post Anti-VEGF Fluorescein Angiographic Patterns in Retinopathy of Prematurity Patients - Jin, Enzhong; Yin, Hong; Liu, Kailin; Liang, Zhiqiao; Zhao, Mingwei (Frontiers in Medicine, 2022)
Purpose: To demonstrate the demographic and treatment characteristics of ROP eyes showed different types of hyperfluorescence in FA initially treated with anti-VEGF agents. Methods: A consecutive case series of ROP treated with anti-VEGF agents were retrospectively studied. All patients underwent fluorescein angiograpy (FA) examinations at least 6 months later after treatment. The demographic and treatment characteristics of eyes with or without hyperfluorescence in FA were analyzed. The different types of hyperfluorescence were divided into three groups including vascular leakage, fibrous membrane and vascular abnormality. Results: Two hundred and forty-two eyes of 123 patients with treatment-required ROP were included. Hyperfluorescence was defined in 51/242 eyes, and 2.08 ± 1.11 injections were performed for them, while the eyes without hyperfluorescence received 1.65 ± 0.80 injections (P=0.013). Vascular leakage was defined in 26/51 hyperfluorescence eyes. The PMA of first injection for the hyperfluorescence group was 38.56 ± 3.24 weeks, which is earlier than that of infants without hyperfluorescence (P=0.011). More additional treatment were performed in eyes with hyperfluorescence (23.53% vs. 3.66%, P=0.000). Among them, the eyes with vascular leakage required more additional treatment than eyes without vascular leakage (42.31% vs. 4.00%, P=0.004) . For the 26 eyes with vascular leakage, 11 eyes of 8 patients received further treatments during further follow-up. No significant difference of refractive errors can be defined between different groups. Conclusion: Eyes with persistent hyperluorescence in FA after treatment required more anti-VEGF and additional treatments including laser and PPV. Not all hyperfluorescences were vascular leakage and required additional treatment.